The Effect of Learning Methods and Class Levels on Improving Creative Thinking in Aviation Vocational: 2x3 Factorial Anova Analysis - B.B Harianto; Rifdian I.S; Edwardo Subagyo (PT FORMOSA CENDEKIA GLOBAL, 2024)
Creative thinking is crucial in aviation vocational education to tackle dynamic industry challenges, but it is often hindered by overly structured educational approaches. This study evaluates the impact of learning methods and class levels on creative thinking enhancement, aiming to improve learning effectiveness in vocational education. Conducted at the Surabaya Aviation Polytechnic with a sample of 144 students selected through multiple-stage random Sampling, data analysis was performed using 2x3 Factorial ANOVA. The results reveal that Problem-Based Learning (PBL) is significantly more effective in enhancing creative thinking compared to conventional methods in aviation vocational education. Class levels (Semester I, II, III) do not significantly influence creative thinking improvement, indicating that longer learning experiences do not automatically boost creativity. Furthermore, no significant interaction was found between learning